The footprint of ship anchoring on the seafloor - Sally J. Watson; Marta Ribó; Sarah Seabrook; Lorna J. Strachan; Rachel Hale; Geoffroy Lamarche (Scientific Reports, 2022)
Abstract With the COVID-19 pandemic came what media has deemed the “port congestion pandemic”. Intensified by the pandemic, the commonplace anchoring of high-tonnage ships causes a substantial geomorphologial footprint on the seabed outside marine ports globally, but isn’t yet quantified. We present the first characterisation of the footprint and extent of anchoring in a low congestion port in New Zealand-Aotearoa, demonstrating that high-tonnage ship anchors excavate the seabed by up to 80 cm, with the impacts preserved for at least 4 years. The calcuated volume of sediment displaced by one high-tonnage ship (> 9000 Gross Tonnage) on anchor can reach 2800 m3. Scaled-up globally, this provides the first estimates of the footprint of anchoring to the coastal seabed, worldwide. Seafloor damage due to anchoring has far-reaching implications for already stressed marine ecosystems and carbon cycling. As seaborne trade is projected to quadruple by 2050, the poorly constrained impacts of anchoring must be considered to avoid irreversible damage to marine habitats.